PROJECT ACTIVITIES IN RUSSIAN LANGUAGE LESSONS - KholmirzaevaSayyoraShukurovna,AshirmatovaManzuraZhumanboevna (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research paper provides design training at Russian language lessons at Tashkent State Agrarian University in conditions are created under which students independently and willingly acquire the missing knowledge from various sources and develop research skills in particular, the ability to identify problems, collect information, observe, and conduct experiment, analysis, hypothesis and generalization.